The Adjustment and Analysis of Manual Synchronization Device and the Circuit for the Million Kilowatts Nuclear Power Plant. (February 2019) - Gao, Da; Li, Jing; Peng, Liying
Abstract: During the twenty-year-overhaul of the Daya bay nuclear power plant unit 1 and unit 2, the overall transformation of the generator outlet circuit breaker was carried out, in which the synchronization device and the circuit is replacement and adjustment. In order to avoid the failure of non-synchronization, static and dynamic tests are required to verify the reliability of synchronization circuit, and finally it have been proved by test.